Criminal Liability Analysis of Physicians Committing Misdiagnosis Through Digital Health Services - Novriandi, Muhammad Reza; Dewi, Yurika F.; Noor, Rico Septian; Pratiwi, Putri Fransiska Purnama (Al-Risalah, 2026)
This study examines the criminal justice system for doctors who misdiagnose patients through digital healthcare services (telemedicine) in Indonesia. With the advancement of information technology in healthcare, digital services offer ease of access, but also pose a potential risk of medical malpractice due to the limitations of in-person physical examinations. The study uses a normative juridical method with a statutory regulatory approach to analyze the relevant regulations and legal consequences of misdiagnosis in the digital context (telemedicine). The study shows that although the Health Law, the Criminal Code, and the Electronic Information and Transactions (ITE) Law regulate the responsibilities and sanctions for medical personnel, specific regulations governing digital healthcare remain unclear and out of sync with technological developments. This creates legal uncertainty, particularly regarding the determination of legal entities responsible for malpractice on digital platforms. Therefore, more specific and comprehensive regulatory reforms are needed to ensure legal certainty, justice, and patient protection, while ensuring the accountability of service providers and medical personnel in telemedicine practices in Indonesia.